2017
DOI: 10.1016/j.aju.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar vs monopolar resection of bladder tumours of >3 cm in patients maintained on low-dose aspirin: A randomised clinical trial

Abstract: ObjectiveTo compare the safety and efficacy of bipolar vs monopolar transurethral resection of bladder tumour (TURBT) in patients maintained on low-dose aspirin with tumours >3 cm.Patients and methodsA prospective randomised single-centre study was performed including 200 patients with bladder tumours of >3 cm, as measured by ultrasonography. All patients were using low-dose aspirin (81 mg/day), which was not stopped in the perioperative period. Patients were randomised into two groups: Group A, monopolar TURB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…Del Rosso et al [7] in a randomised clinical trial showed a significant reduction in the mean (range) hospitalisation time with B-TURBT at 2.2 (2-7) days vs 3.5 (3-6) days in the M-TURBT group (P = 0.008). Hashad et al [20] also reported a significant difference in the mean (SD) postoperative hospital stay in favour of B-TURBT at 31.20 (11.57) vs 42.24 (15.67) h for M-TURBT (P < 0.001) [20]. In our present study, the hospital time was also shorter in the B-TURBT group at 1 day vs the M-TURBT group at 2 days.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Del Rosso et al [7] in a randomised clinical trial showed a significant reduction in the mean (range) hospitalisation time with B-TURBT at 2.2 (2-7) days vs 3.5 (3-6) days in the M-TURBT group (P = 0.008). Hashad et al [20] also reported a significant difference in the mean (SD) postoperative hospital stay in favour of B-TURBT at 31.20 (11.57) vs 42.24 (15.67) h for M-TURBT (P < 0.001) [20]. In our present study, the hospital time was also shorter in the B-TURBT group at 1 day vs the M-TURBT group at 2 days.…”
Section: Discussionsupporting
confidence: 64%
“…Comparable results were obtained by Del Rosso et al [7], whereby bladder perforation was reported in two cases in the monopolar arm and in none in the bipolar arm, with no statistically difference between the groups. Hashad et al [20] also reported bladder perforation in four patients in their monopolar arm and in one patient in the bipolar arm, with no statistical difference between the groups (P = 0.369). Mashni et al [21] reported that no patients developed bladder perforation, with no statistically difference between the groups.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations